2020
DOI: 10.1186/s13059-020-01993-6
|View full text |Cite
|
Sign up to set email alerts
|

Varlociraptor: enhancing sensitivity and controlling false discovery rate in somatic indel discovery

Abstract: Accurate discovery of somatic variants is of central importance in cancer research. However, count statistics on discovered somatic insertions and deletions (indels) indicate that large amounts of discoveries are missed because of the quantification of uncertainties related to gap and alignment ambiguities, twilight zone indels, cancer heterogeneity, sample purity, sampling, and strand bias. We provide a unifying statistical model whose dependency structures enable accurate quantification of all inherent uncer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…We previously demonstrated the superior accuracy of this approach, especially for InDels, compared to widely used somatic variant callers (Narzisi et al, 2018). Moreover, a recently published and independent testing (Köster et al, 2020), showed Lancet to outperform state-of-the-art methods particularly in the detection of twilight zone InDels (30-250 bp).…”
Section: Introductionmentioning
confidence: 92%
“…We previously demonstrated the superior accuracy of this approach, especially for InDels, compared to widely used somatic variant callers (Narzisi et al, 2018). Moreover, a recently published and independent testing (Köster et al, 2020), showed Lancet to outperform state-of-the-art methods particularly in the detection of twilight zone InDels (30-250 bp).…”
Section: Introductionmentioning
confidence: 92%
“…Multi-mapping, for example as done by BWA-MEM, causes unequal genome coverage altering the signal-to-noise ratio 52 . Hence, alignment uncertainty is problematic for accurate SV detection and should be addressed with a sound statistical model 30 , 31 , 52 . Current estimates suggest ~55 Mb of GRCh38 are “dark regions” inaccessible to IL sequencing due to alignment ambiguity (i.e., repeat-rich regions) or the sequencing chemistry (i.e., GC content) 53 .…”
Section: Challenges For Accurate Sv Detection In Cancer Genomesmentioning
confidence: 99%
“…NGS can simultaneously detect different variant types and discover new biomarkers, and is more cost-effective than a series of single-gene assays. Although turn-around times are often longer, sensitivity and precision are maintained 88 provided sufficient sequencing depth is achieved 26 , 31 . As a result, NGS makes pan-cancer biomarker testing feasible, leading to the approval of drugs based on molecular alterations shared by different cancer types like the use of TRK inhibitors for all solid tumors with a NTRK fusion 88 .…”
Section: Multi-platform Data Integration To Improve Detection Of Somamentioning
confidence: 99%
See 2 more Smart Citations